HUBUNGAN ANTARA ORIENTASI RELIGIUS, LOCUS OF CONTROL DAN PSYCHOLOGICAL WELL-BEING MAHASISWA FAKULTAS PSIKOLOGI UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG - Zainul Arifin, In Tri Rahayu (El-QUDWAH, 2011)
The aim of this research are describtion of the correlation between religious orientation, locus of control dan psychological wel-being variables. The sample of this research are 77 students of the 10% all of the population of the students of Psychology Faculty of the Islamic University Maulana Malik Ibrahim in Malang. The instrument in this research had been aplided by the religious orientation scala, locus of control scala and psychological wel-being scala. The describing of the data by descibtion analyzis for the subject of the research, and using the Product Moment Analizing for Correlation between the variables with SPSS 15.00 program. The data of this research shows that, the correlation betwenn religious orientation and  psychological wel-being is xy = 0,350 p = 0,001. Its means is the correlation betwenn religious orientation and psychological wel-being (p0,050), and its mens is too internalized  religious orientation of the sample its soo quick of the frecuency of psychological wel-being. And its mens is too externalized religious orientation of the sample its soo slowly of the frecuency of psychological wel-being.The correlation analyztion of religious orientation and locus of control is rxy =0,534, p=0,000. Its mens is too internalized religious orientation of the sample its soo quick of the frecuency of locus of controle. And its mens is too externalized religious orientation of the sample its soo slowly of the frecuency of locus of controleKey words: psychological well-being